2018
DOI: 10.1038/s41598-018-27390-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective pilot evaluation of vaginal and urine self-sampling for the Roche cobas 4800 HPV test for cervical cancer screening

Abstract: This pilot study sought to evaluate the feasibility of utilizing vaginal self-swabs and urine samples for HPV-based cervical cancer screening in 700 women who had undergone conventional Pap smear screening via the national cervical cancer program in Korea. The cobas 4800 HPV test was utilized to detect HPV in the self-samples. Pap smear results revealed three cases of atypical squamous cells of undetermined significance, 649 cases of negative for an intraepithelial lesion or malignancy, and 48 non-specific inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Another study employing Roche Cobas HPV 4800 assay also reported higher sensitivity in urine samples compared with other HPV DNA tests. 16 Urine contains inhibitors such as nitrites and proteins, which In the present study, the diagnostic performance of urine HPV DNA testing was not assessed among women who are cervical cancer screening nonattenders. We evaluated the test performance of selfcollected urine and vaginal samples in a Gynecologic Oncology clinic, which demonstrated a higher viral load of HPV than the general population.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Another study employing Roche Cobas HPV 4800 assay also reported higher sensitivity in urine samples compared with other HPV DNA tests. 16 Urine contains inhibitors such as nitrites and proteins, which In the present study, the diagnostic performance of urine HPV DNA testing was not assessed among women who are cervical cancer screening nonattenders. We evaluated the test performance of selfcollected urine and vaginal samples in a Gynecologic Oncology clinic, which demonstrated a higher viral load of HPV than the general population.…”
Section: Discussionmentioning
confidence: 90%
“…18 Very few studies compared HPV detection in self-collected urine and vaginal samples globally. 15,16,19,20 Urine self-sampling is more acceptable to nonresponders and is preferred for virological surveillance after HPV vaccination among adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, the accuracy testing of self-sampling and urine sampling methods in our study have not been conducted. Because of the low rates of abnormal cytology (3 cases of atypical squamous cells-undetermined significance), we only identified that the detection rate of HPV 16/18 was 2.0% for vaginal self -sampling and 1.5% for urine sampling, and 99.1% (95% CI=98.1%–99.6%) for overall agreement for HPV 16/18 between the 2 sampling methods [30]. Asciutto et al [31] reported that the relative sensitivities for high-risk HPV detection were 96.4% (93.5%–99.2%) for vaginal self-sampling and 83.9% (78.4%–89.5%) for urine sampling compared to clinician-collected sampling.…”
Section: Discussionmentioning
confidence: 99%
“…The Cobas 4800 HPV Test System consists of 2 parts, i.e., a Cobas x 480 Instrument that is used for automation of nucleic acid purification and PCR sample pipetting and a Cobas z 480 Analyzer that is for automatic real-time PCR amplification and subsequent type-specific hybridization. Although the use of the Cobas 4800 System for HR-HPV testing has been reported in a number of countries [11][12][13][14][15][16], such application in a large population in China has not been documented. In this study, we employed the Cobas 4800 HPV Test System to detect HR-HPV in cervical cytology specimens collected from a total of 5650 asymptomatic women.…”
Section: Introductionmentioning
confidence: 99%